Formas reduzidas da negação no português brasileiro - Lilian Teixeira de Sousa (2007)
This study provides a description and analysis of the reduced forms of preverbal negation in Brazilian Portuguese. The first hypothesis is about a gramaticalization process, with the category change of word, most especially the process whereby items become more grammatical through time. According to gramaticalization literature, the process follows some stages: content item > grammatical word > clitic > inflectional affix > . The studies about the negation reduction show as reduced forms of negation item the full one . nao . and the clitic ones, num and nu. In this study we recognize two more varieties: a nasal vowel ([u. ]) and a nasal following a verb with a vowel in the first syllable,some examples are: nadianta, nimporta. The negation item enasal plus verb f seems to be an affix, the fifth stage of gramaticalization process. The corpus that has been used in the course of this work is composed of interviews with informants from the city of Mariana. The samples were divided in five groups: 1. children, 2. teenagers, 3. young adults, 4. adults and 5. elderly. To test the hypothesis, in a first moment, we proceed to an acoustic analysis of the items duration and, after, a quantitative analysis to check if the variation in the preverbal negation is a change in progress. Trough the acoustic analysis we perceived a gradualnegation reduction; the average for each item was: 150.4 ms to nao, 130.9 ms to num, 80.5 ms to nu and 55 to u. . The quantitative analysis indicated stable variation.